Globalization and Absolute Poverty: A Panel Data Study - Andreas Bergh; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2011)
Using panel data from more than 100 countries around the world from 1988 through 2007, this paper examines the relationship between economic and social globalization and absolute income poverty ex post. We use the globalization index developed by Dreher (2006) and the World Bank poverty estimates. Using a fixed-effect panel based on five-year averages and using a long run first difference regression, we find a robust negative correlation between globalization and poverty. We further examine mechanisms and robustness by separately analyzing the effects of components of economic (trade flows and trade policies) and social globalization (information flows, personal contact and cultural proximity) respectively, controlling for growth, education, inflation, urbanization, and government consumption. Results suggest that information flows and more liberal trade restrictions are robustly negatively correlated with absolute poverty. While growth decreases poverty in the long run, only a small part of the poverty-reducing effect of globalization is mediated via growth.
Keywords: D30; F15; I32; 330; Globalization; Poverty; Panel Data; Armut; Globalisierung; Panel; Welt